Endorsement Sebagai Strategi Pemasaran Ditinjau Dari Etika Bisnis Pada PT Murbey Pasti Sukses (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2021)
Online business is one of method of promoting/offering goods/services that are carried out using the internet network by communicating with each other. In online business, marketing strategies are needed by advertising each product produced thru social media. One of these strategies is endorsement acts. There are several business ethics noted when endorsers or celebrities promote a product through their social media. The purpose of this study was to determine whether the endorsement strategy at PT Murbey Pasti Sukses is in accordance with business ethics. This type of research is qualitative and collected data from PT Murbey Pasti Sukses. The results of the research and discussion can be concluded that the business strategy at PT Murbey Pasti Sukses uses two types of endorsers, namely artists/celebrities and influencers who are active on social media. Endorsements selection choosen by PT Murbey Pasti Sukses considered by shown a good engagement rate. The four strategy indicators (product, promotion, price and people) describe that promotion indicator has a dominant impact to attract consumers' attention and encourage them to buy. Likewise with online business through social media on Instagram at this time, Murbey conducts online promotions using the endorsement system.